Evaluating the Effects of In-Vehicle Side-View Display Layout Design on Physical Demands of Driving. (March 2021) - Beck, Donghyun; Jung, Jaemoon; Park, Woojin
Objective: A driving simulator study was conducted to comparatively evaluate the effects of three camera monitor system (CMS) display layouts and the traditional side-view mirror arrangement on the physical demands of driving. Background: Despite the possible benefits of CMS displays in reducing the physical demands of driving, little empirical evidence is available to substantiate these benefits. The effects of CMS display layout designs are not well understood. Method: The three CMS display layouts varied in the locations of the side-view displays: (A) inside the car near the conventional side-view mirrors, (B) on the dashboard at each side of the steering wheel, and (C) on the center fascia with the displays joined side by side. Twenty-two participants performed a safety-critical lane changing task with each design alternative. The dependent measures were the following: spread of eye movement, spread of head movement, and perceived physical demand. Results: Compared with the traditional mirror system, all three CMS display layouts showed a reduction in physical demands, albeit differing in the types/magnitudes of physical demand reduction. Conclusion: Well-designed CMS display layouts could significantly reduce the physical demands of driving. The physical demands were reduced by placing the CMS displays close to the position of the driver's normal line-of-sight when looking at the road ahead and locating each CMS display on each side of the driver, that is, at locations compatible with the driver's expectation. Application: Physical demand reductions by CMS displays would especially benefit drivers frequently checking the side-view mirrors with large eye/head movements and physically weak/impaired drivers.